Characterization of Gib2 protein interactions in pathogenic fungus cryptococcus neoformans - Ng, Michelle Hui Ping (2015)
The canonical heterotrimeric G protein is comprised of α, β, and γ subunits. The fungal pathogen, Cryptococcus neoformans, encodes three α, one β, and two γ subunits. While the sole canonical β subunit, Gpb1, is involved in mating and haploid differentiation, Gib2 protein acts as an atypical β subunit regulating the conserved cAMP signalling pathway governing virulence in C. neoformans. Gib2 and Gpb1 interact with different α subunits (Gpa1 and Gpa2, respectively), but both interact with γ subunits Gpg1/Gpg2. Gib2 inhibits Ras1 to upregulate cAMP signalling in the absence of Gpa1, and interacts with factors involved in protein synthesis including eIF4A. To gain further insights into the multiple roles of Gib2 and investigate its potential as a drug target, we aimed to characterize Gib2 interactions with its known partners. The protein partners analyzed in this study were found to be poorly expressed and/or insoluble when expressed in a bacterial system. Good soluble expression was obtained only for the His6-MBP-Gpg2 fusion protein, but tag removal was inefficient and the tagged protein did not interact with Gib2 in vitro. Human eIF4A did not interact with Gib2 in vitro either, possibly due to the low sequence similarity between human and C. neoformans eIF4A.